2013
DOI: 10.3324/haematol.2013.087338
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Epstein-Barr virus-related post-transplant lymphoproliferative disease after allogeneic hematopoietic stem cell transplantation

Abstract: © F e r r a t a S t o r t i F o u n d a t i o norder to decrease the lag time for CTL transfer. Among other things, interferon-gamma capture of virus-specific CTL and allogeneic CTL banks containing CTL against the most common HLA haplotypes have been used with some success. 16,22,23 Our group has tried separation of peptide-specific T cells with the help of magnetic beads and MHC multimers. 17,18 Even though this has shown promising results, none of these strategies is yet part of standard clinical practice.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
178
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 49 publications
13
178
3
2
Order By: Relevance
“…This finding is consistent with prior studies reporting PTLD in 0-10% of transplant recipients. 18,[22][23][24] Even if the early introduction of Rituximab initially resolves this complication in most cases, a recent report by Uhlin et al 25 showed that only 20% of patients with PTLD were alive 3 years later. In our study, nine of the 13 patients suffering from this complication died between 4 and 445 days after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with prior studies reporting PTLD in 0-10% of transplant recipients. 18,[22][23][24] Even if the early introduction of Rituximab initially resolves this complication in most cases, a recent report by Uhlin et al 25 showed that only 20% of patients with PTLD were alive 3 years later. In our study, nine of the 13 patients suffering from this complication died between 4 and 445 days after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for developing EBV-PTLD can be considered as existing pre- 20,24,[33][34][35] or developing post-transplant 7,[34][35][36][37] ( Table 3). Importantly, assessing the risk of EBV-PTLD is dependent on the HSCT context with potentially complex interactions between the primary hematological malignancy, HSCT procedure, source, and other factors.…”
Section: Risk Factors For Ebv-ptldmentioning
confidence: 99%
“…Co-infusion of BM-MSCs with cord blood transplantation delays immune reconstitution, as shown by lower levels of T-cell receptor excision circles and serum IgG and IgM. 21 It has further been found to be associated with the development of EBV-related post-transplant lymphoproliferative disorder, 9,22 and invasive fungal infections. 23 There are also worries that MSCs may promote cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%